2023
DOI: 10.1111/jnu.12876
|View full text |Cite
|
Sign up to set email alerts
|

Quality and safety education for nurses: A bibliometric analysis

Abstract: PurposeSince its origin in the United States in 2005, Quality and Safety Education for Nurses (QSEN) has guided nurses' preparation for alleviating preventable harm and improving quality safe care. QSEN's value is illustrated through specific inclusion in the competency‐based 2021 American Association for Colleges of Nursing (AACN) Essentials. The purpose of this bibliometric analysis is to explore publication patterns of the extant QSEN literature to assess QSEN's spread and global penetration and to map the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Quality and safety education has substantially expanded since the incorporation of quality and safety competencies into nursing education 34. In this study, almost every participant reported a safety emphasis within their program of nursing, and 85% have documented that their program has a safety reporting system in place.…”
Section: Discussionmentioning
confidence: 78%
“…Quality and safety education has substantially expanded since the incorporation of quality and safety competencies into nursing education 34. In this study, almost every participant reported a safety emphasis within their program of nursing, and 85% have documented that their program has a safety reporting system in place.…”
Section: Discussionmentioning
confidence: 78%
“…2,8 The 6 QSEN competencies developed were patient-centered care, teamwork and collaboration, evidence-based practice, quality improvement, safety, and informatics. The spread and impact of the QSEN competencies is evident by the adoption within schools of nursing, [9][10][11] the use of the QSEN content in the National State Boards of Nursing Residency programs, 12,13 the Future of Nursing Model, 14 nursing textbooks, [15][16][17][18] statewide initiatives, 19 and by several professional organizations that incorporated the QSEN competencies, such as the Association of periOperative Registered Nurses. 20 Because of the widespread integration of the QSEN competencies in both associate and baccalaureate programs, it is important to understand the overlap between the QSEN competencies and the AACN Essentials.…”
Section: Background Of Qsen Competenciesmentioning
confidence: 99%
“…While nurses constitute "the last line of defense" for patients' safety (Joy, 2009), and as they must take the lead in meeting the failure to rescue challenge that still exists in acute care settings (Burke et al, 2022), we need further understanding of the nature, extent and context of nurses' surveillance interventions and, more importantly, of the impact of such interventions on patient safety (Halverson & Tilley, 2022;Henneman et al, 2012). Now, an initial step in gaining such understanding may be taken by analysing the current corpus of nursing research literature on surveillance and patient safety, assessing in particular the field's critical areas in order to extend the discourse for researchers and practitioners (Sherwood et al, 2023). Given the preceding considerations, and by means of a bibliometric analysis, this study thus aims to:…”
Section: Introductionmentioning
confidence: 99%
“…While nurses constitute “the last line of defense” for patients' safety (Joy, 2009), and as they must take the lead in meeting the failure to rescue challenge that still exists in acute care settings (Burke et al, 2022), we need further understanding of the nature, extent and context of nurses' surveillance interventions and, more importantly, of the impact of such interventions on patient safety (Halverson & Tilley, 2022; Henneman et al, 2012). Now, an initial step in gaining such understanding may be taken by analysing the current corpus of nursing research literature on surveillance and patient safety, assessing in particular the field's critical areas in order to extend the discourse for researchers and practitioners (Sherwood et al, 2023). Given the preceding considerations, and by means of a bibliometric analysis, this study thus aims to: Identify and characterize the most relevant articles, authors, journals and research institutions in the nursing research field with regard to surveillance and patient safety; Identify and characterize the thematic structure of the nursing research field with regard to surveillance and patient safety; Identify and characterize the thematic evolution of the nursing research field with regard to surveillance and patient safety. …”
Section: Introductionmentioning
confidence: 99%